Multi-state polarization switching and multifunction-integrated terahertz metadevice enabled by inverse resonance responses - Deng, Yuwang; Zhou, Qingli; Zhang, Xuteng; Zhang, Pujing; Liang, Wanlin; Ning, Tingyin; Shi, Yulei; Zhang, Cunlin (Frontiers in Physics, 2023)
Dynamical control of terahertz metadevices and integration of versatile functions are highly desired due to increasing practical demands. Here, we propose a multifunctional photosensitive Si hybrid metastructure consisting of twisted split-ring resonator pairs that could empower multi-state polarization switching and object-recognized imaging. The theoretical and simulated results show that inverse complete modulation of cross-polarized components could be realized via tuning the conductivity of the Si-bridge. The calculated ellipticity indicates that our metadevices possess the ability to convert linearly polarized light into left-hand circular-polarized or right-hand circular-polarized waves, as well as left-hand circular-polarized or right-hand circular-polarized into linearly polarized states. Combined with these properties, mono-parameter amplitude imaging and amplitude-phase synergistic encryption imaging are accomplished. Our research provides a new strategy to develop reconfigurable and multifunctional components in the terahertz regime.